Peripheral artery disease is associated with severe impairment of vascular function. (April 2013) - Kiani, Soroosh; Aasen, Jonathan G; Holbrook, Monika; Khemka, Abhishek; Sharmeen, Farhana; LeLeiko, Rebecca M; Tabit, Corey E; Farber, Alik; Eberhardt, Robert T; Gokce, Noyan; Vita, Joseph A; Hamburg, Naomi M
Patients with peripheral artery disease (PAD) have higher cardiovascular event rates than patients with established coronary artery disease (CAD) and abnormal endothelial function predicts cardiovascular risk in PAD and CAD. We investigated the hypothesis that PAD is associated with a greater degree of impairment in vascular function than CAD. We used several non-invasive tests to evaluate endothelial function in 1320 men and women with combined PAD and CAD ( n = 198), PAD alone ( n = 179), CAD alone ( n = 466), or controls aged > 45 years without CAD or PAD ( n = 477). Patients with PAD had lower brachial artery flow-mediated dilation (5.1 ± 3.9% PAD and CAD, 5.9 ± 4.4% PAD alone) compared to patients with CAD alone (7.0 ± 4.5%) and no PAD or CAD (8.1 ± 5.1%, p < 0.0001). In multivariable models adjusting for clinical covariates and the presence of CAD, PAD remained associated with lower flow-mediated dilation ( p < 0.0001). PAD was associated also with lower nitroglycerin-mediated dilation and reactive hyperemia. Patients with both PAD and CAD had a lower digital pulse amplitude tonometry (PAT) ratio in unadjusted models but not in adjusted models. Flow-mediated dilation was modestly associated with PAT ratio in patients with atherosclerotic disease ( r = 0.23, p < 0.0001) but not among control participants ( r = 0.008, p = 0.93). Our findings indicate that patients with PAD have greater impairment of vasodilator function and are consistent with the possibility that endothelial dysfunction may contribute to adverse cardiovascular prognosis in PAD.